Unintended Consequences of Leverage Regulation: Evidence from Korea* - Lee, Woo Jong; Yang, Daniel; Jung, Tae Jin; Kim, Kyung Won (Natalie) (John Wiley and Sons Inc, 2023)
During the 1997 Asian financial crisis,Korean regulators imposed a 200% leverage cap to curb excessive debt and restore economic stability. We examine the real effects and externalities of mandated capital structure changes resulting from this leverage ratio regulation. Our findings indicate that firms that met the leverage requirement experienced a significant decrease in firm risk. However,the effect varied depending on how firms adjusted their capital structure. Firms that chose to issue equity to lower their leverage ratio,as opposed to firms repaying debt,exhibited higher firm risk,lower investment-q sensitivity,and lower profitability in the post-regulation period. © 2023 Korean Securities Association.
Keywords: Asian financial crisis; Capital structure; G32; G38; Regulation; Target leverage; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico; ODS 16 - Paz, justicia e instituciones sólidas